The Relationships of Nurse Staffing Level and Work Environment With Patient Adverse Events. Issue 1 (7th December 2015) - Cho, Eunhee; Chin, Dal Lae; Kim, Sinhye; Hong, OiSaeng
Abstract: Purpose: The purpose of this study was to examine the relationships of nurse staffing level and work environment with patient adverse events. Design: This cross‐sectional study used a combination of nurse survey data ( N = 4, 864 nurses), facility data ( N = 58 hospitals), and patient hospital discharge data ( N = 113, 426 patients) in South Korea. Methods: The three most commonly nurse‐reported adverse events included administration of the wrong medication or dose to a patient, pressure ulcers, and injury from a fall after admission. Multilevel ordinal logistic regression was employed to explore the relationships of nurse staffing level (number of patients assigned to a nurse) and work environment (Practice Environment Scale of the Nursing Work Index) with patient adverse events after controlling for nurse, hospital, and patient characteristics. Findings: A larger number of patients per nurse was significantly associated with a greater incidence of administration of the wrong medication or dose (odds ratio [OR] = 1.01, 95% confidence interval [CI] = 1.007–1.016), pressure ulcer (OR = 1.01, 95% CI = 1.007–1.016), and patient falls with injury (OR = 1.02, 95% CI = 1.013–1.022). A better work environment had a significant inverse relationship with adverse events; the odds of reporting a higher incidence of adverse events were 45% lower for administration of the wrong medication or dose (OR = 0.55, 95% CI = 0.400–0.758), followed by 39% lower for pressure ulcer (OR = 0.61, 95% CI = 0.449–0.834) and 32% lower for falls with injury after admission (OR = 0.68, 95% CI = 0.490–0.939). Conclusions: This study found that a larger number of patients per nurse and poor work environment increase the incidence of patient adverse events, such as administration of the wrong medication or dose to a patient, pressure ulcers, and injury from falling after admission. The findings suggest that South Korean hospitals could prevent patient adverse events by improving nurse staffing and work environment. Clinical Relevance: Healthcare strategies and efforts to modify adequate nurse staffing levels and better work environments for nurses are needed to improve patient outcomes.